Conditional Dynamics and the Multihorizon Risk-Return Trade-Off. (22nd April 2021) - Chernov, Mikhail; Lochstoer, Lars A; Lundeby, Stig R H
Abstract: We propose testing asset pricing models using multihorizon returns (MHRs). MHRs effectively generate a new set of test assets that is endogenous to the model and that identifies a broad set of possible conditional misspecifications. We apply MHR-based testing to prominent linear factor models and show that these models typically do a poor job of pricing longer-horizon returns, with pricing errors that are similar in magnitude to the risk premiums they were designed to explain. We trace the errors to the conditional factor dynamics. Explicitly incorporating factor timing into the models often makes mispricing worse, thereby posing a challenge for future research.